Inflammatory process: factors inducing inflammation, forms and manifestations of inflammation, immunological significance of the inflammatory reaction - Harvanová, Gabriela; Duranková, Silvia (Alergologia Polska - Polish Journal of Allergology, 2025)
Current knowledge gained in research and clinical settings suggests that inflammation is a cause or concomitant of every disease process in the body. Inflammation is a term used to describe complex processes at different levels. These processes are triggered in the body when there are structural or functional disturbances that threaten the existence of the organism. The role of inflammation is to activate processes aimed not only at the destruction of harmful substances but also at the restoration of damaged structures. It is a genetically encoded protective response and therefore occurs in every individual. Inflammatory cells contain specific types of sensor receptors that allow them to recognize the presence of foreign substances and their own damaged cells. During the inflammatory response, active substances important in defence against foreign agents or even against one’s own structures are formed. The formation of substances is regulated to reduce the risk of damage to the body’s tissues.